MAIN ASPECTS OF TEACHING PHARMACEUTICAL CHEMISTRY BASED ON THE COMPETENCY-BASED APPROACH AT THE PROFESSIONAL COLLEGE OF BSMU - Велика, Алла; Кропельницька, Юлія; Гарвасюк, Олександра (SWorldJournal, 2025)
At the present stage, the rapid development of the pharmaceutical industry requires high-quality training of competent specialists who will be competitive in the labor market. This involves not only the in-depth acquisition of knowledge, skills, and abili